Urbanization and agricultural productivity: some lessons from European cities. (1st February 2018) - Oueslati, Walid; Salanié, Julien; Wu, JunJie
Abstract: This article evaluates the effect of increasing urbanization on agricultural productivity at the rural-urban fringe for a set of European metropolises. It takes into account changes in total developed area, population density and the level of urban fragmentation associated with urbanization. To cope with endogeneity issues related to urban equilibrium covariates, we set up an instrumental variables strategy based on historical and institutional instruments. Our results indicate that increasing population density increases agricultural productivity at the rural-urban fringe, while increasing urban fragmentation may have a detrimental effect on agricultural productivity at low levels of fragmentation. We use instrumental variable Bayesian model averaging (IVBMA) to address model uncertainty and use an alternative panel dataset to confirm our instrumental strategy. Our results are robust to alternative model specifications and estimation methods.